Pengetahuan Remaja Tentang Kesehatan Reproduksi di SMA X Jember - Dini Kurniawati; Tirsa Intania Dewi; Eka Afdi Septiyono (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2024)
Adolescents' knowledge of reproductive health is a crucial aspect of overall health, encompassing physical, mental, and social well-being. Adolescents aged 15-18 are in a stage of physical, emotional, and cognitive development that is not yet fully mature but characterized by high curiosity. This study aimed to describe the level of knowledge about reproductive health among adolescents at SMA X Jember. This study used a descriptive qualitative approach, with data collected through a Google Form questionnaire distributed to 103 students from grades X and XI at SMA X Jember in June 2024. Data analysis was conducted using descriptive statistical methods to depict the level of adolescents' knowledge about reproductive health. The results showed that 91.3% of the 103 respondents had a good level of knowledge about reproductive health, consisting of 47 females and 56 males aged between 15-18 years. All respondents (100%) had been exposed to reproductive health information from various sources. The study concluded that the level of knowledge about reproductive health among adolescents at SMA X Jember was good for both females and males. Easy access to information from various sources strengthened this level of knowledge.